Specific Detection and Imaging of Enzyme Activity by Signal‐Amplifiable Self‐Assembling 19F MRI Probes. Issue 38 (16th August 2013) - Matsuo, Kazuya; Kamada, Rui; Mizusawa, Keigo; Imai, Hirohiko; Takayama, Yuki; Narazaki, Michiko; Matsuda, Tetsuya; Takaoka, Yousuke; Hamachi, Itaru
Abstract Specific turn‐on detection of enzyme activities is of fundamental importance in drug discovery research, as well as medical diagnostics. Although magnetic resonance imaging (MRI) is one of the most powerful techniques for noninvasive visualization of enzyme activity, both in vivo and ex vivo, promising strategies for imaging specific enzymes with high contrast have been very limited to date. We report herein a novel signal‐amplifiable self‐assembling 19F NMR/MRI probe for turn‐on detection and imaging of specific enzymatic activity. In NMR spectroscopy, these designed probes are "silent" when aggregated, but exhibit a disassembly driven turn‐on signal change upon cleavage of the substrate part by the catalytic enzyme. Using these 19F probes, nanomolar levels of two different target enzymes, nitroreductase (NTR) and matrix metalloproteinase (MMP), could be detected and visualized by 19F NMR spectroscopy and MRI. Furthermore, we have succeeded in imaging the activity of endogenously secreted MMP in cultured media of tumor cells by 19F MRI, depending on the cell lines and the cellular conditions. These results clearly demonstrate that our turn‐on 19F probes may serve as a screening platform for the activity of MMPs.